Evaluasi Proses Pembelajaran Dengan Pendekatan Systems Thinking - Casnan Casnan; Purnawan Purnawan; Irman Firmansyah; Heti Triwahyuni (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
A quality learning process is a learning process developed based on the results of the evaluation. One of the evaluations of the learning process is the systems thinking approach. This study aims to determine the constraints of the learning process with systems thinking approach and determine problem-solving strategies to improve the quality of the learning process. The research method used is a descriptive qualitative method and group model building. Based on the results of the study, it shows that the objective variable in the learning process is student understanding, the supporting variable to better understand the lecture material is the creativity of the lecturer.